(untitled) (Research, Society and Development, 2020)
The International Union of Pure and Applied Chemistry (IUPAC, 2016) established 2019 as the international year of the Periodic Table, taking into account its 150-year "anniversary". With this century and a half of evolutions in this instrument and its use for teaching chemistry, we questioned how we can approach the concepts involved so that we avoid being a teacher of the last century, paraphrasing Kalinke (1999). In this article, we aim to make an inventory of apps for Android smartphones that can be used to build knowledge related to the periodic table. Ten applications from the Android operating system store were selected, searching for the terms ‘Periodic Table’, ‘Applications’ and ‘Games’; the identification, technical and conceptual aspects were analyzed. Suggestions of use and main functionalities of the apps were marked for the teaching community, in order to make a first contact with these technologies and be stimulated to approach them in moments of knowledge construction.